Damage Potential and Feeding Preference of Halyomorpha halys (Stål), Nezara viridula (L.), and Leptoglossus zonatus (Dallas) Among Different Ripening Stages of Tomato - Md Tafsir Nur Nabi Rashed; Adam G. Dale; Gideon Alake; Simon S. Riley; Nicole Benda; Amanda C. Hodges (Insects)
Tomato (Solanum lycopersicum L.) is one of the most preferred hosts of polyphagous stink bugs (Hemiptera: Pentatomidae) and leaf-footed bugs (Hemiptera: Coreidae). These hemipterans can infest tomato fruits at all stages of fruit ripening. However, it is unclear whether there is any feeding preference for these true bugs among different ripening stages of tomato (green, breaker, pink, and red stages). Feeding and behavioral assays were performed to determine the feeding preference and damage potential of two common stink bugs—the brown marmorated stink bug (Halyomorpha halys (Stål)) and the southern green stink bug (Nezara viridula L.)—and a leaf-footed bug (Leptoglossus zonatus (Dallas)) among the various ripening stages of tomato. The results indicated that green is the most preferred ripening stage for N. viridula and L. zonatus, while pink tomatoes were found to be a more preferred feeding site for H. halys. Fully ripe red tomatoes were found to be the least preferred feeding site for all three insects. The findings of this study will be useful for developing fruit damage symptom-based monitoring programs and establishing economic threshold levels for these pests in tomatoes, as well as informing harvesting regimes.